The Dawn of Aurora Kinase Research: From Fly Genetics to the Clinic - Carmena, Mar; Earnshaw, William C.; Glover, David M. (Frontiers in Cell and Developmental Biology, 2015)
Aurora kinases comprise a family of highly conserved serine-threonine protein kinases that play a pivotal role in the regulation of cell cycle. Aurora kinases are not only involved in the control of multiple processes during cell division but also coordinate chromosomal and cytoskeletal events, contributing to the regulation of checkpoints and ensuring the smooth progression of the cell cycle. Because of their fundamental contribution to cell cycle regulation, Aurora kinases were originally identified in independent genetic screens designed to find genes involved in the regulation of cell division. The first aurora mutant was part of a collection of mutants isolated in C. Nusslein-Volhard’s laboratory. This collection was screened in D. M. Glover’s laboratory in search for mutations disrupting the centrosome cycle in embryos derived from homozygous mutant mothers. The mutants identified were given names related to the “polar regions”, and included not only aurora but also the equally famous polo. Ipl1, the only Aurora in yeast, was identified in a genetic screen looking for mutations that caused chromosome segregation defects. The discovery of a second Aurora-like kinase in mammals opened a new chapter in the research of Aurora kinases. The rat kinase AIM was found to be highly homologous to the fly and yeast proteins, but localised at the midzone and midbody and was proposed to have a role in cytokinesis. Homologs of the equatorial Aurora (Aurora B) were identified in metazoans ranging from flies to humans. Xenopus Aurora B was found to be in a complex with the chromosomal passenger INCENP, and both proteins were shown to be essential in flies for chromosome structure, segregation, central spindle formation and cytokinesis. Fifteen years on, Aurora kinase research is an active field of research. After the successful introduction of the first anti-mitotic agents in cancer therapy, both Auroras have become the focus of attention as targets for the development of new anti-cancer drugs. In this review we will aim to give a historical overview of the research on Aurora kinases, highlighting the most relevant milestones in the advance of the field.